Simulator assessment of innovative intersection designs on driver speeds and trajectories. (October 2022) - Kekez, Damir; Walton-Blane, Alison; Picen, Tanya; Vinci, Bradley; Bonner, Adrian; Albrecht, Matthew A.; Black, Melissa H.
Highlights: Five novel intersection designs were evaluated in a driving simulator experiment. Speed reductions were observed for all intersections when driving at speed. Beneficial modification of conflict angles were seen for the curved designs. Age and gender had complex but modest effects on driver behaviour. Abstract: Intersections are over-represented in crash statistics internationally, suggesting that treatments targeting intersections could substantially improve road safety. Aligning with a Safe Systems approach, several innovative intersection configurations have been proposed. We evaluated the effectiveness of five designs on reducing speed and modifying conflict angles using a driving simulator. The designs were 1) cut-through, 2) modified restricted squircle, 3) unrestricted squircle, 4) raised approach, and 5) raised intersection. For the higher speed green light condition, speed reductions for vehicles travelling straight through the intersection were seen for all five innovative designs on approach to the intersection and at critical conflict points within the intersection. Within the intersection specifically, speed reductions ranged from 1) 7–8 km/h for the modified restricted squircle, 2) 12.5–16.5 km/h for the unrestricted squircle, raised approach, and raised intersection, and 3) 15–19 km/h for the cut-through. In contrast, speeds for drivers turning right were either not substantially reduced (modified restricted squircle, unrestricted squircle, and raised intersection) or were increased (raised approach and cut-through). Beneficial modification of conflict angles were also observed at conflict points for three of the five designs: cut-through, and two variations of the squircle design. Innovative intersection designs may be effective in reducing intersection crash risk by reducing speeds and conflict angles.